2021
DOI: 10.1021/acsapm.0c01236
|View full text |Cite
|
Sign up to set email alerts
|

UV-Resistant Trifluoropropyl-Substituted Open-Cage Silsesquioxane-Pendant Polysiloxanes

Abstract: We prepared three types of tris(dimethoxysilyl)-heptatrifluoropropyl-substituted open-cage silsesquioxanes, namely hepta (3,3,3trifluoropropyl)-substituted open-cage silsesquioxanes (IC-POSSs) attached to three dimethoxysilyl groups by linkers of variable lengths at the opening vertex (TFP-Hdi, TFP-Vdi, and TFP-Adi). The dimethoxysilyl groups allowed subsequent hydrolysis and polycondensation under mild conditions to form flexible siloxane bonds. The structures of the resulting trifluoropropyl-substituted open… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…With the continuous exploration of the Earth and extraterrestrial space, human beings are exposed to increasingly extreme environments, among which ultralow temperature conditions are one of the main challenges. Silicone elastomers, characterized by exceptional resistance to high and low temperatures, radiation, , and ultraviolet light, , as well as insulation, air permeability, , and physiological inertness properties, find widespread application in various fields, including electronic/electrical, aerospace, petrochemical, construction, transportation, and daily chemical industries. Notably, ethyl silicone rubber has attracted increasing attention as the elastomer material with the lowest known glass transition temperature. , Derived from the cross-linking of linear polydiethylsiloxane (PDES), with −Si–O–Si– as the main chain and –CH 2 CH 3 as the side group, ethyl silicone rubber exhibits a glass transition temperature of −145 °C.…”
Section: Introductionmentioning
confidence: 99%
“…With the continuous exploration of the Earth and extraterrestrial space, human beings are exposed to increasingly extreme environments, among which ultralow temperature conditions are one of the main challenges. Silicone elastomers, characterized by exceptional resistance to high and low temperatures, radiation, , and ultraviolet light, , as well as insulation, air permeability, , and physiological inertness properties, find widespread application in various fields, including electronic/electrical, aerospace, petrochemical, construction, transportation, and daily chemical industries. Notably, ethyl silicone rubber has attracted increasing attention as the elastomer material with the lowest known glass transition temperature. , Derived from the cross-linking of linear polydiethylsiloxane (PDES), with −Si–O–Si– as the main chain and –CH 2 CH 3 as the side group, ethyl silicone rubber exhibits a glass transition temperature of −145 °C.…”
Section: Introductionmentioning
confidence: 99%
“…31−34 Polysiloxanes were well known for their excellent biocompatibility and stability. 35,36 Researchers favor polysiloxanes due to their biocompatibility, fascinating stability, and rich source depth. In addition, owing to its ease for functionaliza-tion and green synthesis, polysiloxanes promise to serve as ideal platforms for bioimaging.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Polysiloxanes were well known for their excellent biocompatibility and stability. , Researchers favor polysiloxanes due to their biocompatibility, fascinating stability, and rich source depth. In addition, owing to its ease for functionalization and green synthesis, polysiloxanes promise to serve as ideal platforms for bioimaging. To fill this gap, we have constructed a polysiloxane fluorescent probe that could switchable target subcellular organelles and efficiently detects ONOO – based on the advantages of polysiloxane.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the symmetrical structure of CC-POSS, corner-opened POSS (CO-POSS) exhibits three silanol groups in the open moiety. 8 We have been developing CO-POSS materials through the functionalization of the three silanol groups, such as main-chain polymers, 9 side-chain polymers, 10 network polymers, 11 and nanofillers. 12 During a series of investigations, we found that CO-POSSs exhibit thermal stability comparable to that of the corresponding CC-POSS while the symmetry is effectively reduced.…”
Section: Introductionmentioning
confidence: 99%